Aksi Kolektif Petani Dalam Koperasi Untuk Agribisnis Berkelanjutan - Hariance, Rika (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2019)
Social exchange assumes social behavior is an exchange series where individuals always try to maximize the benefits they get and minimize the costs or risks incurred. The social exchange theory is perfected with network theory (social exchange theory), which is that social exchange does not only occur between two people (individuals and individuals), but occurs by involving various parties, agencies, and organizations. This study aims to describe the collective action in agribusiness partnerships that have been carried out by several previous researchers. The method used in this research is a literature study by looking at patterns and symptoms from previous research. This research tries to complete an important part in a cooperative namely collective action as a basis for the establishment of cooperatives.